Optimization of Parameters for a More Efficient Use of Adipose-Derived Stem Cells in Regenerative Medicine Therapies - Meire Aguena; Roberto Dalto Fanganiello; Luiz Alexandre Lorico Tissiani; Felipe Augusto André Ishiy; Rodrigo Atique; Nivaldo Alonso; Maria Rita Passos-Bueno (Hindawi Limited, 2012)
Adipose tissue-derived stem cells (ASCs) association to fat in autologous lipotransfer is promising for a more effective soft tissue reconstruction, and optimization of protocols to isolate ASCs from lipoaspirate fat is much needed. We demonstrated that an increase in adipocyte differentiation is dependent on the number of ASCs. In a sample of 10 donors, we found a higher concentration of nucleated cells in the lower abdomen compared to flank (P=0.015). In a sample of 6 donors we did not find differences in the cell yield obtained by manual or pump-assisted aspiration (P=0.56). We suggest that the increase in the number of ASCs in the reinjected fat may enhance the efficiency of newly formed adipose tissue and that the anatomical region from which to harvest fat tissue needs to be considered to optimize the number of ASCs in the harvested tissue. Finally, pump-assisted aspiration can be used without any significant harm to the viability of cells.